The effectiveness between of yoga and birth ball in reducing labor pain: a systematic review - Hartati, Devi; Jannah, Bayti; Sulasdi, Nur Ain Desta; Sinaga, Sri Putriani; Sulistyaningsih; Hafidz, Firdaus (BKM Public Health and Community Medicine, 2024)
Purpose: Identify the effectiveness between Yoga and birth ball in decreasing labor pain intensity. Methods: This study used a systematic review design with the PRISMA-SR checklist. This systematic review referred to three steps, namely, (1) search strategy, (2) selection criteria, and (3) data extraction and quality assessment. The article search used 2 databases: ScienceDirect and Pubmed and ResearchRabbit. Results: Of 14 articles, 7 discuss Yoga's effectiveness in diminishing labor pain, and another 7 discuss birthing balls' efficacy in alleviating labor pain. Yoga and birth balls effectively reduce childbirth pain intensity. Conclusion: Besides, a combination of Yoga and birth ball or a combination of birth balls and counterpressure or free position when entering childbirth reduces labor pain. Yoga could also be combined with back massage, aromatherapy, or hypnosis. Future studies are expected to analyze the level of effectiveness between birthing balls and Yoga in reducing labor pain intensity in both developing and developed countries.